Precautionary Saving, Insurance, and the Origins of Workers' Compensation - Kantor, Shawn Everett; Fishback, Price V. (Journal of Political Economy, 1996)
In this article we test whether the introduction of social insurance has led to a reduction in private insurance purchases and precautionary saving by examining the introduction of workers' compensation. Our empirical analysis is based on the financial decisions of over 7,000 households surveyed for the 1917-19 Bureau of Labor Statistics Cost-of-Living study. We find that the presence of workers' compensation at least partially crowded out private accident insurance and led to a substantial reduction in precautionary saving. The introduction of workers' compensation caused private saving to fall by approximately 25 percent, with other factors held constant.